Purslane: A Perspective Plant Source Of Nutrition And Antioxidant - Md Kamal Uddin; Li Quan; Md Mahmudul Hasan; Motmainna; Mohammed Selamat Madom (2020)
Purslane (Portulaca oleracea) is a leafy vegetable that most likely originated in the Mediterranean region. It is a rich source of potassium, magnesium and possesses the potential to be used as vegetable source of omega-3 fatty acid and recently has been recognized as the richest source of a-linolenic acid, essential omega-3 and 6 fatty acids, ascorbic acid, glutathione, atocopherol and b-carotene. The stems and leaves also have high energy values which is 303.9 Kcal/100g dry weight. Mineral contents (mg/100gm DM) were K (14.71), Na (7.17), Ca (18.71), Fe (0.48) and Zn (3.02). P. oleracea has higher total phenolic and antioxidant content than plants at immature stages. The antioxidant content and nutritional value of purslane are important for human consumption. It revealed tremendous nutritional potential and has indicated the potential use of this herb for the future.